Cambios bioquímicos, microbiológicos y sensoriales en el chame Dormitator latifrons (Richardson, 1844) sometido a anhidrobiosis bajo dos ambientes climatizados - Bermúdez-Medranda, Alexandra Elizabeth (2025)
The chame Dormitator latifrons is a symbolic species associated with rural aquaculture in coastal regions of the South American Pacific. Its adaptation to stay alive out of water (anhydrobiosis) for days is beneficial for its storage and transport at room temperature. The aim of the study was to determine the tolerance of chame to anhydrous conditions. Sixty chames were distributed in containers and kept in two climate-controlled environments at 16 and 24 °C for 96 h. Survival, malondialdehyde levels, total proteins and pH in the muscles and lactate dehydrogenase (LDH) activity in the gills were monitored. Additionally, the behaviour of the fish was monitored, as well as the total number of microorganisms with a sensory evaluation. The critical period of survival occurred after 48 h, where the pH decreased, and the MDA levels increased. The number of microorganisms increased in both environments and the sensory evaluation showed a loss of freshness at 24 °C. LDH activity is linked to the activation of anaerobic metabolism and is a sign of gill deterioration. The results of biochemical, microbiological and sensory analyses indicate that the first 48 h of exposure to anhydrobiosis comprise the period of maintenance of the freshness of D. latifrons, which may be key for its post-harvest handling and sale.